Sowards, Ed., Makers Of The Western Tradition - Portraits From History - Luehrs, Robert (Teaching History: A Journal of Methods, 1995)
Social history ("history from below," "the history of daily life," or, as George M. Trevelyan described it better than half a century ago, "the history of a people with the politics left out") is scarcely a new field Its antecedents may be discerned in the works of the Father of History, Herodotus, who enlivened his story of the struggle between East and West with wonderful if not always accurate accounts of the eccentric habits and curious mores of the various ethnic groups who populated the Persian Empire. Even so, social history along with such affiliates as women’s history and ethnic studies now seems to be entering a veritable golden age.